Effects of six-week land-based and aquatic-based plyometric training programe on power, agility, dynamic balance and muscle soreness of basketball players - مهران کارگر; حمید معرفتی; محمدرضا امیر سیف الدینی; علیرضا سلیمی (فیزیولوژی ورزش و فعالیت بدنی)
Introduction: Plyometric exercises have been shown to increase strength and explosiveness in athletesparticipating. Aquatic exercises have been noted to have beneficial effects; however there has been littleresearch conducted comparing plyometrics in a land-based and an aquatic-based setting. Method: Thirty threebasketball players, (age, 19.39±0.99; weight, 82.36±9.4; BMI, 22.16±2.17) based on their vertical jump andtraining history were randomly divided into aquatic plyometric, land based plyometric, and control group. Thesix-week protocol for the experimental groups was conducted following aspecific program twice a week. three3x3 factorial designs for vertical jump, dynamic balance and the illinois tests with two experimental groups anda control group, and two 2x4 factorial design for the DOMS test with two experimental groups. Resultssuggested that the aquatic- and land-based groups significantly (P<0.05) outperformed the control group in thevertical jump. There were no significant diffrences among dynamic balance and agility performance for threegroup (P>0.5). For delay onset muscle soreness, there was a significant diffrence for the land by aquatic groupsin the first and end week (P<0.05). Conclusion: in conclusion, aquatic-based and land-based plyometrictraining has been shown similar effects on performance. Also aquatic therapy may help to decrease muscularsoreness while performing exercises. However, more research needs to be conducted to determine the affects ofplyometric training in the aquatic setting.